An Application of KMV Model to Forecast the Credit Risk of Corporate Customers andBank’s Expected Losses - Nguyen, Thi Canh (University of Economics Ho Chi Minh City, 2023)
The research aims to apply KMV-Merton model to calculate and forecast default probability (DP) among corporate customers of Vietcombank. Analyzing data from financial statements of 6,398 corporate customers in the years 2008–2012/2013, the research shows that the DP of the whole customer portfolio is 2.6%, equaling a loss of VND6,319 billion, or 3.8% of outstanding loans to the portfolio. The results also show that small-sized companies have smaller DP as compared to larger ones. Regarding industries, the lowest DP is found in road and waterway transport business, and the highest is in electricity (including production, transmission and distribution), production of other kinds of power, and seafood processing business. Industries with high DP and outstanding loans may cause the greatest damage to banks. The research concludes that large-sized companies and seafood processing enterprises cause the greatest losses to banks.